Utilization of Short Tandem Repeat Analysis to Resolve Specimen Mislabeling in the Anatomic Pathology Laboratory. (28th October 2021) - Tenney, T; Robinson, B; Sullivan, H C
Abstract: Introduction/Objective: A mislabeled specimen is an example of preanalytical error that can have significant consequences on patient care. These errors can be difficult to detect and resolve. One method to confirm genetic identity is short tandem repeat (STR) analysis, which is utilized in forensic investigations, paternity studies, and post- hematopoietic stem cell transplantation monitoring. Herein we present application of STR analysis to resolve a suspected specimen mislabeling prior to receipt in our anatomic pathology laboratory. Methods/Case Report: DNA was extracted from paraffin embedded tissues. Chimerism testing was performed by STR analysis using the Globalfiler (ThermoFisher Scientific) and analyzed by Chimermarker (Softgenetics) automated chimerism software. Results (if a Case Study enter NA): Colon biopsies were received for a single patient (#1) with two requisition forms. Each specimen (A-F) was labeled with the patient's name, with specimens A-D noted on first page of requisition and specimens E-F on the second requisition page. After the case was signed out, the lab was contacted looking for biopsy results on another patient (#2) who was seen on the same day as patient #1. Review of all the patients seen in the endoscopy suite on the given date raised suspicion that specimens E-F from the second page of the requisition actually pertained to patient #2. STR analysis performed on specimens confirmed that specimens E-F were genetically distinct from those labelled A-D. Tissue from a subsequent biopsy on patient #2 was analyzed by STR testing, which was identical to STR results performed on specimens E-F. Conclusion: Here we utilized STR testing to resolve a suspected mislabeled specimen, allowing the appropriate diagnosis to be attributed to the correct patient. This is a unique application of a common method, which could be implemented in anatomic pathology laboratories to resolve cases of specimen mix-ups.